Class 1C antiarrhythmic drugs in atrial fibrillation and coronary artery disease. (24th January 2020) - Pantlin, Peter G.; Bober, Robert M.; Bernard, Michael L.; Khatib, Sammy; Polin, Glenn M.; Rogers, Paul A.; Morin, Daniel P.
Abstract: Background: Class 1C antiarrhythmic drugs (AADs) are effective first‐line agents for atrial fibrillation (AF) treatment. However, these agents commonly are avoided in patients with known coronary artery disease (CAD), due to known increased risk in the postmyocardial infarction population. Whether 1C AADs are safe in patients with CAD but without clinical ischemia or infarct is unknown. Reduced coronary flow capacity (CFC) on positron emission tomography (PET) reliably identifies myocardial regions supplied by vessels with CAD causing flow limitation. Objective: To assess whether treatment with 1C AADs increases mortality in patients without known CAD but with CFC indicating significantly reduced coronary blood flow. Methods: In this pilot study, we compared patients with AF and left ventricular ejection fraction ≥50% who were treated with 1C AADs to age‐matched AF patients without 1C AAD treatment. No patient had clinically evident CAD (ie, reversible perfusion defect, known ≥70% epicardial lesion, percutaneous coronary intervention, coronary artery bypass grafting, or myocardial infarction). All patients had PET‐based quantification of stress myocardial blood flow and CFC. Death was assessed by clinical follow‐up and social security death index search. Results: A total of 78 patients with 1C AAD exposure were matched to 78 controls. Over a mean follow‐up of 2.0 years, the groups had similar survival ( P  = .54). Among patients with CFC indicating the presence of occult CAD (ie, reduced CFC involving ≥50% of myocardium), 1C‐treated patients had survival similar to ( P  = .44) those not treated with 1C agents. Conclusions: In a limited population of AF patients with preserved left ventricle function and PET‐CFC indicating occult CAD, treatment with 1C AADs appears not to increase mortality. A larger study would be required to confidently assess the safety of these drugs in this context.